Analisis Peran Agen Perubahan dalam mengatasi Anak berkasus Seksualitas melalui Penguatan Pembiasaan Karakter - Hermaini , Budi; Sardjiyo, Sardjiyo (Antroposen: Journal of Social Studies and Humaniora, 2022)
The purpose of this study is to analyze the role of change agents in dealing with children with sexuality cases through character habituation. Change agents include educational agents and social agents. This study uses a literature approach or literature review, which contains articles relevant to agents of change, juvenile delinquency, and character habituation, which were obtained from various journals accredited by Sinta 6-2. The results of this study found that agents of change (1) educational institutions, (2) teachers, (3) families, (4) environment, (5) media play a role in changing children's character. The conclusion of this study shows that agents of change play a very large role in the character of children, especially in schools. Through habituation of character both at school and in the social environment, it is able to achieve character changes for children, especially in the case of child sexuality